2010
DOI: 10.1021/nl1005492
|View full text |Cite
|
Sign up to set email alerts
|

Using Highly Accurate 3D Nanometrology to Model the Optical Properties of Highly Irregular Nanoparticles: A Powerful Tool for Rational Design of Plasmonic Devices

Abstract: The realization of materials at the nanometer scale creates new challenges for quantitative characterization and modeling as many physical and chemical properties at the nanoscale are highly size and shape-dependent. In particular, the accurate nanometrological characterization of noble metal nanoparticles (NPs) is crucial for understanding their optical response that is determined by the collective excitation of conduction electrons, known as localized surface plasmons. Its manipulation gives place to a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 46 publications
1
69
0
Order By: Relevance
“…In fact, it has been shown that the exact shape of the gold triangle plays an important role in the distribution of the resulting near-field. 24 Furthermore, our simulations suggest that the optical environment (in this case especially the thickness of the SiO 2 layer) is also of great importance for the near-field distribution. All simulations have been carried out with the commercially available software package FDTD Solutions (Lumerical Solutions, Inc.) […”
Section: Experimental Setup For Time-resolved X-ray Scatteringmentioning
confidence: 78%
See 1 more Smart Citation
“…In fact, it has been shown that the exact shape of the gold triangle plays an important role in the distribution of the resulting near-field. 24 Furthermore, our simulations suggest that the optical environment (in this case especially the thickness of the SiO 2 layer) is also of great importance for the near-field distribution. All simulations have been carried out with the commercially available software package FDTD Solutions (Lumerical Solutions, Inc.) […”
Section: Experimental Setup For Time-resolved X-ray Scatteringmentioning
confidence: 78%
“…In fact, it also suffered from a less detailed input of the boundary conditions (concave particle walls, rounding of the edges, and dielectric constant of the substrate). The importance of an exact modeling of a given nanostructure for the outcome of calculations has recently been shown by Perassi et al 24 Furthermore, the experimental premises in Refs. 7 and 9 are not exactly the same.…”
Section: A Pattern Formationmentioning
confidence: 99%
“…3D models based on the numerical methods such as the discrete dipole approximation (DDA), the finite difference time domain (FDTD) method, and FEM have been used to simulate the near-field intensity distribution of metallic nanostructures with arbitrary geometries by solving the Maxwell's equations numerically [45][46][47][48]. Compared with other numerical methods, 3D-FEM shows high accuracy for modeling irregular structures and simulating fine elements within large domains.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…ET based on these imaging modes is nowadays often performed in an automated or semi-automated manner and is routinely employed for the study of morphology and distribution of features in 3D (e.g. [4][5][6][7]). …”
Section: Introductionmentioning
confidence: 99%